STRATEGI PENGEMBANGAN USAHATANI JAGUNG DI KABUPATEN TANAH LAUT, PROVINSI KALIMANTAN SELATAN - Petrus Suse Kobesi; Hairi Firmansyah; Windi Bunga Devita; Ody Wolfrit Matoneng; Andri Sarifuddin (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
The food sector plays a strategic role in agricultural development and overall national development. Demand for food continues to increase along with population growth and increasing per capita income. This study aims to identify strategies for developing corn farming in Tanah Laut Regency. The method used by the researcher is a SWOT analysis, and strategy priority determination is carried out using QSPM analysis. The results of the analysis found six main strategies, including: 1) Increasing farmers' understanding of good corn cultivation techniques, including pest and disease control, thereby minimizing the risk of crop failure. 2) Strengthening farmer group institutions for more effective coordination between related institutions. 3) Optimizing farmer resources to increase production while meeting industrial market needs. 4) Maximizing government support to maintain production continuity. 5) Optimizing corn productivity with high quality (grade) as an effort to deal with price fluctuations in the market. 6) Expanding farmers' access to financing sources or agricultural capital to support the application of appropriate technology.